Moral Injury and Its Consequences Among Combat Veterans: Preliminary Findings on the Role of Moral Judgment - Faigenbloom, Dor (Journal of interpersonal violence, 2025)
Exposure to potentially morally injurious events (PMIEs) among combat veterans has been acknowledged as a significant stressful combat event that may lead to various mental health problems, including depression and moral injury (MI), outcomes of shame and guilt. Recent studies have examined both risk and protective factors that can contribute to PMIEs and their consequences. However, while the general level of one’s moral judgment is a logical contributor to moral injuries, it has yet to be examined empirically. In the current study, we examined the unique impact of moral judgment levels on the experience of PMIEs among combat veterans. We also examined the moderating role of moral judgment in the relationship between PMIEs and MI outcomes and depressive symptoms. A volunteer sample of 70 male Israeli combat veterans completed self-report questionnaires and a moral judgment task in a cross-sectional design study. Our findings indicate that moral judgment contributed to higher levels of perceiving others’ actions as transgressive (PMIE-Other), above and beyond combat exposure. Moreover, we found that moral judgment has a moderating role in the link between PMIEs and their negative outcomes: Among veterans with higher levels of moral judgment, the association between PMIEs and their expressions was stronger than for those with lower levels of moral judgment. Our finding highlights the unique contribution of moral judgment level to PMIEs and their mental health consequences. It can be cautiously suggested that moral judgment should be viewed as a pre-recruitment risk factor that can help identify those at greater risk for mental health problems following exposure to PMIEs.